Foraging habitat selection by breeding Herring Gulls (Larus argentatus) from a declining coastal colony in the United Kingdom. (31st October 2021) - Clewley, G.D.; Barber, L.J.; Conway, G.J.; Clark, N.A.; Donato, B.J.; Thaxter, C.B.; Burton, N.H.K.
Abstract: Individual foraging specialisms among generalist species can have important consequences for demographic rates. We investigated the habitat preferences of breeding Herring Gulls ( Larus argentatus ) at South Walney, a declining coastal colony in the UK, comparing results to a previous assessment made three decades before, when the breeding population was higher, which indicated substantial use of terrestrial, intertidal and anthropogenic resources. We used a two-stage Resource Selection Function (RSF) analysis to assess the habitat selection of 21 Herring Gulls fitted with GPS tags over three breeding seasons (2014–16). By generating pseudo-absences within the minimum convex polygon surrounding individual level GPS fixes, we first used logistic regression models to relate presence/absence for each individual to habitat. Selection for mussel bed areas was also modelled specifically as a function of phase of tide, time of day, period within the breeding season, year as well as individual covariates of mass, sex and hatching success. Second, individual RSF coefficients were extracted from the logistic regression models and used as response variables in linear models. Herring Gulls significantly selected for mussel beds and other coastal habitats (75% of all fixes away from the colony occurring in these habitats). Selection for mussel bed sites was significantly greater during the first half of the breeding season, March–May, compared with June–August, while there was also significant positive selection for this habitat between −3 and −2 m tide height (ordnance datum). There has been an apparent reduction in the range of food resources utilised by Herring Gulls at South Walney in recent years with a greater propensity for intertidal specialists within the tracked sample and, in particular, little use was made of urban and landfill areas. Therefore, better understanding of the intertidal resources available and considered management will be beneficial to balance the needs of conservation and commercial and social interests of the nearby shellfisheries. Highlights: There has been a reduction in the range of food resources utilised by Herring Gulls at a declining colony in recent years. There was a greater propensity for intertidal specialists with few individuals exploiting anthropogenic food resources. Understanding foraging preferences can inform both conservation goals and interactions with commercial shellfisheries.